Arthroscopic Management of Glenohumeral Arthritis: A Joint Preservation Approach. Issue 21 (1st November 2018) - Millett, Peter J.; Fritz, Erik M.; Frangiamore, Salvatore J.; Mannava, Sandeep
Abstract : Treatment of young, active patients with primary glenohumeral osteoarthritis (GHOA) is challenging because shoulder arthroplasty may not be ideal in this population. In the past two decades, joint-preserving arthroscopic management options for GHOA, including débridement, have been used to treat different pathologies related to GHOA to reduce pain, to improve function, and to delay or even avoid arthroplasty. Key aspects of comprehensively addressing GHOA arthroscopically include chondroplasty, synovectomy, loose body removal, humeral osteoplasty with excision of the goat's beard osteophyte, capsular release, subacromial and subcoracoid decompression, axillary nerve decompression, and biceps tenodesis. Although data are still emerging, clinical studies report that an arthroscopic approach to glenohumeral arthritis using these various procedures reduces pain, improves function, and improves clinical outcome scores in the short- to mid-term follow-up period. Additional high-level studies are warranted to evaluate long-term outcomes and durability following this procedure.